The challenge of maintaining necessary vascular and endovascular services at a referral center in Northern Italy during the COVID-19 outbreak. (August 2021) - Piazza, M; Xodo, A; Squizzato, F; Conti, G De; Boemo, D; Carretta, G; Grego, F; Antonello, M
Objectives: The Padova Hospital Vascular Surgery Division is located in Veneto, one of the area of the Northern Italy most hit by the Coronavirus disease 2019 outbreak. The aim of this paper is to describe the protocols adopted and to evaluate their impact during the acute phase of Coronavirus spread, focusing on the management of elective and urgent/emergent surgery, outpatients activity, and also health staff preservation from intra-hospital Coronavirus disease 2019 infection. Methods: Several measures were progressively adopted in the Padova University Hospital to front the Coronavirus disease 2019 outbreak, with a clear strong asset established by 9 March 2020, after the Northern Italy lockdown. Since this date, the Vascular Surgery Unit started a "scaled-down" activity, both for elective surgical procedures and for the outpatient Clinical activities; different protocols were developed for health preservation of staff and patients. We compared a two months period, 30 days before and 30 days after this time point. In particular, emergent vascular surgery was regularly guaranteed as well as urgent surgery (to be performed within 24 h). Elective cases were scheduled for "non-deferrable" pathology. A swab test protocol for COVID-19 was applied to health-care professionals and hospitalized patients. Results: The number of urgent or emergent aortic cases remained stable during the two months period, while the number of Hospital admissions via Emergency Room related to critical limb ischemia decreased after national lockdown by about 20%. Elective vascular surgery was scaled down by 50% starting from 9 March; 35% of scheduled elective cases refused hospitalization during the lockdown period and 20% of those contacted for hospitalization where postponed due to fever, respiratory symptoms, or close contacts with Coronavirus disease 2019 suspected cases. Elective surgery reduction did not negatively influence overall carotid or aortic outcomes, while we reported a higher major limb amputation rate for critical limb ischemia (about 10%, compared to 4% for the standard practice period). We found that 4 out of 98 (4%) health-care providers on the floor had an asymptomatic positive swab test. Among 22 vascular doctors, 3 had a confirmed Coronavirus disease 2019 infection (asymptomatic); a total of 72 swab were performed (mean = 3.4 swab/person/month) during this period; no cases of severe Coronavirus disease 2019 (deaths or requiring intensive care treatment) infection were reported within this period for the staff or hospitalized patients. Conclusions: Elective vascular surgery needs to be guaranteed as possible during Coronavirus disease 2019 outbreak. The number of truly emergent cases did not reduce, on the other side, Emergency Room accesses for non-emergent cases decreased. Our preliminary results seem to describe a scenario where, if the curve of the outbreak in the regional population is flattened, in association with appropriate hospitals containment rules, it may be possible to continue the activity of the Vascular Surgery Units and guarantee the minimal standard of care.